Understanding the Dynamics of Poliomyelitis Spread in Pakistan - Atta Abbas NAQVI; Syed Baqir Shyum NAQVI; Nida YAZDANI; Rizwan AHMAD; Niyaz AHMAD; Fatima ZEHRA (Tehran University of Medical Sciences, 2017)
Understanding the Dynamics of Poliomyelitis Spread in Pakistan